Investigation into the determinants of outward cross-border mergers and acquisitions by GCC countries: A macroeconomic perspective. - Ellithy, Ahmed/A (2016)
With increasing levels of foreign investments, the majority of studies have focused on the role of the host country towards attracting inflows of foreign direct investment (FDI) within the context of the developed world. This thesis examines to what extent do home country macroeconomic factors affect outward cross border M&A by the Gulf Cooperation Council (GCC) countries from the period of 1995-2015. In order to investigate into this topic, different quantitative regression models were used: Pooled Ordinary Least Squares (POLS), Random effects model (REM), Fixed effects model (FEM) and negative binomial regression. The results indicate that home country macroeconomic variables including GDP, trade openness, inflation, interest rates and liquidity are significant determinants of outward international M&A deals by the GCC economies. Finally, the limitations and suggested future research lines are presented.